THE INFLUENCE OF MASTICATION TO CURING CHARACTERISTIC OF NATURAL RUBBER AND PHYSICALPROPERTIES OF ITS VULCANIZATES - Abu Hasan; Rochmadi Rochmadi; Hary Sulistyo; Suharto Honggokusumo (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
THE INFLUENCE OF MASTICATION TO CURING CHARACTERISTIC OF NATURAL RUBBER AND PHYSICALPROPERTIES OF ITS VULCANIZATES. The research on the mastication that influences the curing characteristic of natural rubber and physical properties of its vulcanizates has been conducted. The research started from rubber mastication with variation of carbon black filler addition into rubber compound. Rubber compound was then measured to identify its curing characteristic using rheometer and tested its viscosity using Mooney viscosity tester. Physical properties of rubber vulcanizates such as abrasion resistance, tear strength, and elongation at break were also measured. The results indicated that curing characteristic tended to decrease, while only scorch time tended to increase from B1, B2, B3 and B4. Elongation at break tended to decrease, while tear resistance and abrasion resistance tended to increase from B1, B2, B3 and B4. Mooney viscosity of the compound also tended to decrease. It can be concluded that B1 is better than B2, B3 and B4. However, if rubber vulcanizates require high tear resistance and abrasion resistance, such as for shoes sole and tread of tire, then B4 is the most appropriate vulcanizate.